2005
DOI: 10.1136/jnnp.2004.039974
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of tuberculum sellae meningiomas: involvement of the optic canal and visual outcome

Abstract: To present a large series of surgically treated tuberculum sellae meningiomas with particular regard to involvement of the optic canal and visual outcome. Methods: A retrospective analysis was done on 53 patients (40 female) with meningiomas originating from the tuberculum sellae who underwent surgery between 1991 and 2002. The standard surgical approach consisted of pterional craniotomy. Sixteen meningiomas extended posteriorly onto the diaphragma sella, 29 anteriorly to the planum sphenoidale, and 19 to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
127
1
6

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(141 citation statements)
references
References 22 publications
7
127
1
6
Order By: Relevance
“…Unaddressed residual tumors left within the optic canal after surgery could result in persistent visual loss, visual deterioration, and future tumor recurrence. 56 This has led to several authors in recommending early optic nerve decompression and removal of intracanalicular tumor, which has resulted in favorable visual outcomes. 2,5,14,27,29,43,44,49,51,55,56 Visual improvement has been reported as high as 78%-91% in some series.…”
Section: Optic Canal Involvement In Tuberculum Sellae Meningiomasmentioning
confidence: 99%
See 1 more Smart Citation
“…Unaddressed residual tumors left within the optic canal after surgery could result in persistent visual loss, visual deterioration, and future tumor recurrence. 56 This has led to several authors in recommending early optic nerve decompression and removal of intracanalicular tumor, which has resulted in favorable visual outcomes. 2,5,14,27,29,43,44,49,51,55,56 Visual improvement has been reported as high as 78%-91% in some series.…”
Section: Optic Canal Involvement In Tuberculum Sellae Meningiomasmentioning
confidence: 99%
“…43,55 Access to the optic canals is critical not only for visual outcome, but also for extent of resection, as unaddressed residual tumor in the optic canal can be a source of recurrence or failure of visual improvement. 56 Various transcranial surgical approaches to remove tuberculum sellae meningiomas include unilateral or bilateral subfrontal, bifrontal interhemispheric, supraorbital, eyebrow keyhole supraorbital, frontolateral, frontotemporal/pterional, orbitopterional, and orbitozygomatic approaches. 3,5,11,23,24,29,36,43,[46][47][48][49][50]55 More recently, there has been interest in endonasal extended transsphenoidal approaches (microscopic, microscopic with endoscopic assistance, and purely endoscopic) to remove tuberculum sellae meningiomas.…”
mentioning
confidence: 99%
“…However, the percentage of improvement was significantly higher in patients who presented symptoms for less than six months compared with those whose symptoms had lasted for one year. Schick and Hassler 21 reported on a series of 53 patients with TSMs; 20 patients improved, 25 patients remained unchanged, and seven patients worsened. Statistical analyses allowed these authors to conclude that postoperative recovery of the visual deficit was worst in older patients and in patients in whom the duration of symptoms was longer than six months.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the removal of the orbital bar and orbital roof, the decompression of the optic nerve via clinoidectomy, the unroofing of the optic canal, and the opening of the falciform ligament have contributed to the significant postoperative improvement of the visual function of these patients 11,17,18,21,[23][24][25] . Ohta et al 10 reported on 21 cases of complete resection of TSMs in a series of 33 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation